Keberkesanan pembelajaran koperatif (STAD) ke atas pemahaman, komunikasi, pencapaian dan sikap matematik bagi topik pecahan murid sekolah rendah daerah Sarikei, Sarawak - Wong, Nguok Ling (2017)
This study aims to investigate the comprehension, communication, attitude and effects of Student Teams-Achievement Division (STAD) cooperative learning on Mathematics achievement in Sarikei District, Sarawak. This study also explore the students’ and teachers’ perceptions of STAD cooperative learning. The number of subjects involved this study is seventy students from Year Five in Sarikei District, Sarawak. A total of 35 students were involved in the experimental group (20 males & 15 females) while another 35 students were involved in the control group (19 males & 16 females). Data collection was done twice which were the pretest and the post test. The gap between the exam was four weeks. The Mathematics test has 20 items which consists of 10 comprehension items and another 10 communication items. The questions were adapted from the Primary School Achievement Test (Ujian Pencapaian Sekolah Rendah). Mathematics attitude was measured using 19 items, while the 20 items used to measure students’ attitude on STAD. Semi-structured interviews and observations were used to obtain students’ and teachers’ views on STAD cooperative activities and learning. Data were analyzed using SPSS version 19 technique ANCOVA. The findings shown that the use of STAD techniques in Mathematics learning towards comprehension, communication, and Mathematics attitude can improves Mathematics achievement. Additionally, this study has also shown main effect and direct interaction in comprehension, communication, and students’ Mathematics achievement and attitude in post test between the experimental and control groups. This suggests that STAD cooperative learning plays an active pedagogical role to improve comprehension, communication, as well as Mathematics achievement and attitude. Interviews show that STAD cooperative learning increases interest, motivation and Mathematics knowledge sharing among students as compared with conventional learning. Observation of teaching and learning using STAD in the classroom shows that student-student and student-teacher interaction is strengthened. STAD encourages the students and teachers to be innovative and creative in improve teaching and learning of Mathematics in the classroom. These benefit the students in Sarikei District and enable them to compete healthily with the other students from urban areas in Mathematics.